Multi-Element Fingerprinting Combined with Chemometrics for Identification of Seaweeds and Innovative Risk–Benefit Assessment - Yuansheng Guo; Tiantian Zuo; Shuo Gong; Anzhen Chen; Hongyu Jin; Jing Liu; Qi Wang; Jingjing Liu; Shuai Kang; Ping Li; Feng Wei; Shuangcheng Ma (Foods)
Seaweeds are one of the major marine foods with high values. The diversity of seaweed species significantly impacts their quality and is closely linked to their purity and safety. For the first time, this study established a model to discriminate seaweed species using a multi-element fingerprinting approach for species identification. Twenty-nine elements derived from seaweeds were analyzed. Chemometrics showed that seaweed samples could be well separated by the established multi-element fingerprints, of which Ag, Mn, Sr, and K were the most important variables for discrimination. Furthermore, the present study proposed an innovative risk–benefit assessment strategy for seaweeds that considers both risks and benefits, developing a novel risk–benefit assessment model from both dietary and medicinal perspectives for the first time. Our innovative strategy was well-conceived to accurately and effectively differentiate seaweeds based on species and scientifically evaluate both benefits and risks associated with seaweeds. This strategy is poised to offer invaluable insights into the sustainable growth of the seaweed sector and to bolster public health initiatives, ensuring a robust and forward-looking approach to both industry and healthcare advancements.